The management of asthma in the phenotype and biomarker era: The proposal of a new diagnostic-therapeutic model - Blasi, Francesco; Bettoncelli, Germano; Canonica, Giorgio Walter; Centanni, Stefano; Crimi, Nunzio; DiMaria, Giuseppe; Gasparini, Stefano; Gentili, Gilberto; Girbino, Giuseppe; Mereu, Carlo; Minghetti, Paola; Nardini, Stefano; et al. (The Journal of asthma, 2016)
Treatment goals in asthma patients are the achievement of a good control of symptoms and the reduction of the risk of exacerbation. However, a "one-size-fits-all" therapeutic strategy is no longer appropriate to effectively pursue these goals, due to the heterogeneity of asthma. To make the treatment scenario even more complex, asthma patients often present comorbidities that may alter response to therapy. In addition, adherence to asthma treatment is poor. Given this complex and heterogeneous picture, the management of asthma is highly challenging. A clear diagnostic-therapeutic model of patients' care and the definition of the specific responsibilities of different healthcare providers appear necessary to improve clinical outcomes and better allocate healthcare resources. We present here a proposal for this model.